2016
DOI: 10.5897/ajar2016.10809
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of yield losses caused by glyphosate in soybeans with biostimulant

Abstract: Enhanced selectivity can be achieved for some herbicide treatments through the application of chemicals that reduce or protect plants from injuries. The objective of this work was to evaluate the potential to prevent herbicide yield losses in glyphosate-resistant soybean by the use of the biostimulant Fertiactyl PÓS. Based on results from two field experiments, the association of Fertiactyl PÓS with glyphosate applied post emergence of soybeans reduced foliar injuries and prevented yield losses caused by the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…This phenomenon can possibly be explained by the fact that the plant had been exposed to a greater period of time in which to metabolize the herbicide, which could ultimately have interfered with crop growth. Other studies have already reported that the sequential application of glyphosate, whether isolated or in conjunction with other herbicides, can cause reductions in crop yield (ALONSO et al, 2010;CONSTANTIN et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This phenomenon can possibly be explained by the fact that the plant had been exposed to a greater period of time in which to metabolize the herbicide, which could ultimately have interfered with crop growth. Other studies have already reported that the sequential application of glyphosate, whether isolated or in conjunction with other herbicides, can cause reductions in crop yield (ALONSO et al, 2010;CONSTANTIN et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…In soybean cultivars with glyphosate tolerance, the occurrence of symptoms of damage is visible after the application of glyphosate (ALONSO et al, 2011;CONSTANTIN et al, 2016). Even with the transgenic insertion of the gene that codifies the EPSPS enzyme (which allows the plant to manifest an enzyme which is not sensitive to the aforementioned active ingredient; (BECKIE; HALL, 2014), the plant is not capable of totally detoxifying glyphosate in certain situations, or there are observable secondary symptoms derived from the herbicide's phytotoxic action, such as the chelating action of glyphosate, leading to symptoms of deficiency in the micronutrients manganese, iron, and zinc (SERRA et al, 2011;ZOBIOLE et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations